Rat peripheral blood leucocyte reaction in the age aspect on the background of metabolic syndrome experimental modeling - N. A. Shutova (Kazimierz Wielki University, 2020)
The purpose of the research is to investigate links between body mass index and changes in the leucocyte formula of peripheral blood in rats of different ages in experimental modeling of nongenetic alimentary obesity with subsequent MS development; to identify possible associations between these indicators in animals depending on age. Contingent and research methods. Metabolic syndrome was reproduced according to the developed method in rats of different age groups by combining high-fat and high-carbohydrate diet in parallel with pharmacological correction of physiological satiation inhibition. Results. It is determined that the mechanisms of low gradient chronic inflammation development in adipose tissues on the background of metabolic syndrome differ from classical inflammatory response mechanisms. Weight gain is associated with the activation of various leucocyte forms depending on age and degree of mass increase. Young rats have body mass index associated with the amount of peripheral blood neutrophils and more delayed in time; adult animals have body mass index associated with eosinophils, starting from the first month of metabolic syndrome development; old animals have body mass index associated with monocytes and lymphocytes, during the whole period of the trial. The dependence of inflammatory reaction symptoms on the age and sex of the animal on the background of obesity is confirmed by the present associative links (peripheral blood cell composition - animal's age - body mass index) and can be determined later, as a marker factor for metabolic syndrome development.